Minimal increases of serum alpha‐foetoprotein herald HCC detection in Caucasian HBV cirrhotic patients under long‐term oral therapy. (12th August 2019) - Loglio, Alessandro; Iavarone, Massimo; Viganò, Mauro; Orenti, Annalisa; Facchetti, Floriana; Cortinovis, Ivan; Lunghi, Giovanna; Ceriotti, Ferruccio; Occhipinti, Vincenzo; Rumi, Mariagrazia; Sangiovanni, Angelo; Colombo, Massimo; et al.
Abstract: Background & Aims: In Caucasian patients with compensated cirrhosis caused by hepatitis B virus (HBV), the risk of hepatocellular carcinoma (HCC) developing persist despite long‐term nucleos(t)ide analogs (NUC) treatment. In the surveillance of this population with persistently normal transaminases because of NUCs, the added value of serum alpha‐foetoprotein (AFP) monitoring is poorly defined. Methods: Two hundred and fifty‐eight Caucasian HCC‐free patients with HBV‐compensated cirrhosis who started tenofovir or entecavir while having normal serum AFP levels (≤7 ng/mL) at baseline or within the first year of treatment underwent HCC surveillance by semiannual ultrasound evaluation and serum AFP determination. Results: During 96 (18‐120) months of antiviral therapy, 3947 AFP values were collected, median AFP level was 2 ng/mL. Thirty‐five patients developed an HCC at an overall 8‐year crude cumulative incidence of 14% (annual incidence of 2%). HCC incidence increased in parallel with increasing AFP thresholds: 24%, 36%, 64% and 92% for AFP levels after exceeding 2, 4, 6 and 7 ng/mL for the first‐time. Of the 12 patients who experienced an AFP rise > 7 ng/mL, 11 developed an HCC and one had liver metastases of lung cancer. Overall, an AFP > 7 ng/mL had 99.6% specificity, 31.4% sensitivity, 91.7% PPV, 90.2% NPV, LR+ 70.1 and LR− 0.69 for HCC; this excellent specificity was maintained up to 18 months before HCC detection. Conclusions: In Caucasian patients with HBV‐compensated cirrhosis on long‐term NUC, an increase in AFP over 7 ng/mL shows excellent specificity, heralding HCC development within 1 year.